Elucidating differences between two confusing Shorea contorta S. Vid and Pentacme mindanensis Foxw. species of Dipterocarpaceae via leaf morphometrics: An initial investigation - Mazo, Kean Roe F; Aribal, Lowell G (Bangladesh Journal of Plant Taxonomy, 2020)
Abstract not available Bangladesh J. Plant Taxon. 27(2): 461-465, 2020 (December)